Consistency in Standalone Canaloplasty Outcomes Using the iTrack Microcatheter - Khaimi MA; Koerber N; Ondrejka S; Gallardo MJ (Clinical Ophthalmology, 2024)
Mahmoud A Khaimi,1 Norbert Koerber,2 Simon Ondrejka,2 Mark J Gallardo3 1Dean McGee Eye Institute – Oklahoma Health Center, Oklahoma City, OK, USA; 2Augencentrum Köln, Köln, Germany; 3El Paso Eye Surgeons, PA, El Paso, TX, USACorrespondence: Mahmoud A Khaimi, Dean McGee Eye Institute – Oklahoma Health Center, 608 Stanton L Young Blvd, Oklahoma City, OK, 73104, USA, Tel +1 405-271-6060, Email mahmoud-khaimi@dmei.orgPurpose: To study the consistency in outcomes of standalone canaloplasty performed via an ab-interno surgical technique in reducing intraocular pressure (IOP) and number of medications in uncontrolled open-angle glaucoma (OAG) eyes over a 12-month period.Methods: This retrospective multicenter case series included patients who underwent standalone canaloplasty via an ab-interno surgical technique using the iTrack microcatheter (Nova Eye, Inc., Fremont, USA) and had preoperative uncontrolled OAG (IOP≥ 18mmHg) along with no previous glaucoma surgery. The iTrack microcatheter is used to circumnavigate 360° and viscodilate Schlemm’s canal. Consistency of IOP and medications reduction on an eye-by-eye basis were evaluated to understand the outcomes in each single eye.Results: Sixty-four eyes of 60 patients (age 71.5± 13.4 years) were included. Six eyes (9%) that underwent additional glaucoma surgery were considered a failure and were subsequently excluded from analysis. At 12 months, IOP was reduced in 57 of the 58 (89%) remaining eyes; one eye had the same IOP with a reduced number of medications. Of the 57/58 eyes with a reduced IOP: 44 eyes (69%) required fewer medications; 12 eyes (19%) required the same number of medications. Of these 58 eyes, 78% of eyes had a ≥ 20% reduction in IOP compared to baseline; 69% eyes had a postoperative IOP ≤ 15 mmHg, and 86% eyes ≤ 18 mmHg at 12 months. Forty percent of the eyes were medication-free at 12 months compared to none at baseline.Conclusion: Canaloplasty performed via an ab-interno surgical technique as a standalone procedure consistently reduced IOP and glaucoma medications in almost all eyes.Keywords: canaloplasty, iTrack, microcatheter, viscodilation, intraocular pressure, open-angle glaucoma